AN ANALYSIS FIGURATIVE LANGUAGE IN WHITE SWAN SONG LYRICS - I Kadek Dita Wahyu Dwi Pratama; Gede Irwandika (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
This study aims to find out the types of imagery and the meaning of imagery in the White Swans album Cygnus. Ten songs by White Swan served as the data source. This study used an observational method to collect the data. In this study, a descriptive qualitative method was used to analyze the data. This study applied the theory proposed by Knickerbocker and Reninger (1963) to find out the types of figurative language. To answer the second problem, this study used Leech's (1981) theory of meaning, which focused on analyzing the data source based on the types of meaning, such as conceptual meaning and connotative meaning. The result of this study shows that 20 dates contained imagery. Based on the analysis, this study found 6 types of imagery in the White Swan Cygnus album. There are 6 (30%) exaggeration data, 4 (20%) metaphor data, 4 (20%) personification data, 4 (20%) simile data, 1 (5%) metonymy data, and 1 (5%) data on the paradox. The results of this study are equally dominant imagery found in the Cygnus White Swan album such as B. Hyperbola with a total of 6 (30%). It can be found dominant as exaggerations used in context can enhance the ability to understand the message being sent by the speaker and generally convey the feelings or emotions. The results emphasize the album's symbolic representation and the significance of deciphering its meaning. This work expands our understanding of musical imagery and provides new directions for future investigation.